The Threat of Virality Manipulation in Social Media Towards Deliberative Democracy - Widyatama, Rendra; Ananda, Vidya; Wiratmo, Liliek Budiastuti (Universitas Semarang, 2024)
Introduction: The use of social media as a channel for political communication is becoming increasingly common in modern society. Some users seek virality to influence public opinion. Among them, some employ manipulative tactics to achieve virality, which can undermine deliberative democracy. Unfortunately, the impact of manipulative virality on deliberative democracy has not received sufficient attention. This study aims to describe how manipulative virality poses a threat to deliberative democracy. The researchers focus on five social media platforms–X, Instagram, Facebook, TikTok, and YouTube, because Indonesians widely use these for political communication. Methods: The researchers use a qualitative, exploratory approach, focusing on relevant documents using interpretive analysis and observation to study of X, Instagram, Facebook, TikTok, and YouTube. Findings: Research identifies four methods of manipulative virality that undermine deliberative democracy: using fake accounts, deploying bots, paying buzzers, and spreading hoaxes. These practices threaten and subvert deliberative democracy by creating false appearances of support, potentially distorting public opinion, misleading policymakers, and damaging society. Manipulative virality often benefits wealthy groups, as they can afford to pay buzzers and deploy bots, unlike poorer groups. Originality: This study explores the role of social media in public discourse to promote deliberative democracy. It offers novelty by presenting an in-depth analysis that digital media has the potential to undermine deliberative democracy due to the use of bots, fake accounts, and paid influencers. The findings emphasize the importance of preserving authentic public dialogue while addressing unethical practices that manipulate social media for personal or political gain.